Die "kanon" in die kanon as probleem vir die prediking - Dreyer, T. F. J. (Hervormde teologiese studies, 1988)
The problem of preaching in terms of a 'canon' within the canon New evidence in scientific research, attempts to prove that Holy Scripture no longer maintain its unqualified position as an authoritive canon. The authority and relevancy of certain books and passages are questioned. There are significant signs that a 'canon' within the canon is already functioning in the preaching of the church. How does this mere fact of a 'canon' within the canon, affects and influences the preaching of today? The paper is an attempt to define the problem and to provide guidelines in handling this contemporary question.